Objectives and main features of establishing a special economic zone in the region - Turaev, Sarvar (THE INNOVATION ECONOMY, 2024)
This article presents scientifically based proposals and recommendations on the processes of socio-economic development of regions by attracting local and foreign investments on the main goals and objectives of creating special economic zones. Issues aimed at improving methodological support for implementation and justifying the goals and main features of creating a special economic zone in the regions were also covered. “Special economic zones are limited territories, cities, sea and air ports, where special preferential economic conditions are applied for domestic and foreign entrepreneurs, facilitating the solution of foreign trade, general economic, social, scientific, technical and scientific-technological issues. Special economic zones carry out economic, innovative, resource, organizational and social functions within the framework of ensuring economic stability and social well-being of the state. The functions of the special economic zone have the characteristics of continuity, production of goods and services for consumers, the formation of new ideas, new tools, factors and technologies, rational and effective integration of resources and factors of production, implementation of tactical measures and strategic goals. The creation of special economic zones serves to increase the number of entrepreneurs in society, create jobs, improve the standard of living and social status of workers. These questions are reflected in the article